CHARACTERISTICS ABSORPTION AND MODELING OF UNRIPE PLANTAIN CHIPS - A. Ajala; F. Ajala (Nusa Putra University, 2018)
In this study, water absorption characteristics of dried unripe plantain chips were investigated by soaking in distill water at 20°C, 30°C and 40°C. The data generated were fitted into three models namely Peleg, Weibull and exponential. The statistical criteria used in evaluation of the models were coefficient of determination (R2), reduced chi-square (χ2), mean bias error (MBE) and root mean square error (RMSE). The result shows that temperature did not affect water absorption properties initially, but it did affect it as re-hydration progressed. The result of R2 shows that Weibull model has the highest value of 0.979 and exponential model has lowest value of 0.653. Therefore, Weibull model was adjudged to have successfully fitted water absorption of unripe plantain chips.